Searching for Treatment - Martin Obradovits; hilipp Plaickner (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2020)
When experts have superior information on their customers' needs and appropriate treatment/repair/advice is a credence good, there are obvious incentives for opportunistic behavior. What compounds this is that experts regularly make treatment recommendations and price offers only after consumers have approached them, creating additional market power due to search costs. In our model, an expert enjoys monopoly power on diagnosis and major treatments, but has limited market power on minor treatments due to fringe competition. The expert's treatment offer only gets revealed to consumers upon visit, and both searching the expert and fringe firms is costly. For search costs that are not excessively high, in equilibrium the expert inappropriately proposes major treatment to all or a fraction of low-severity consumers, which they respectively accept all or some of the time. Next to wasteful overtreatment, further inefficiencies arise in the latter case, as some high-severity consumers mistakenly leave the expert, and some low-severity consumers incur unnecessary search costs. Total welfare is non-monotonic in search costs and may even be maximized when these are large. Expert competition often does not, or only partly, alleviate market distortions.
Keywords: D43; D82; D83; L13; L15; 330; Expert Service; Credence Goods; Search; Treatment; Overtreatment; Repair; Advice